Raven's gate - Horowitz, Anthony, 1955- (New York : Scholastic, 2005)
Sent to live in a foster home in a remote Yorkshire village, Matt, a troubled fourteen-year-old English boy, uncovers an evil plot involving witchcraft and the site of an ancient stone circle.
"Apple series.".
Prequel to: Evil star.
Booklist starred.
School Library Journal.
Wilson's Junior High School.
5.0
Keywords: Fantasy; Foster home care -- Fiction; Good and evil -- Fiction; Identity -- Fiction; Stone circles -- Fiction; Supernatural -- Fiction; Witches -- Fiction; Foster home care -- Fiction; Good and evil -- Fiction; Individuality -- Fiction; Monuments -- Fiction; Supernatural -- Fiction; Witches -- Fiction; England -- Fiction; Yorkshire (England) -- Fiction; England -- Fiction; Yorkshire (England) -- Fiction; Fantastic fiction